Allelopathic effects of actinobacterial isolates on seed germination and early seedling growth of velvetleaf (Abutilon theophrasti Medik.) - Šantrić, Ljiljana R; Radivojević, Ljiljana; Gajić Umiljendić, Jelena; Sarić-Krsmanović, Marija (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
This study aimed to examine in vitro allelopathic effects of actinobacterial isolates on seed germination and early seedling growth of velvetleaf (Abutilon theophrasti). Thirtyfive actinobacterial isolates were obtained from soil and compost in different phases of composting. Also, an experiment variant involving the herbicide mesotrione was set in the recommended amount of application, as a reference standard. The experimental results indicate statistically significant differences (p<0.05) between controls and all treatments with actinobacterial isolates regarding seed germination, and radical and shoot length. The highest inhibition (100%) was observed in seed germination and radical length in treatments with the isolates A10 and NOV2, compared to uninoculated starch casein broth (SCB) as control. Shoot length was shown to be the most sensitive parameter, where 100% inhibition was observed in the following treatments with actinobacteria: A010, A017, NOV2, NOV3, NOV4 and NOV5. Actinobacterial isolates showed a higher inhibitory effect on seed germination than treatment with the reference herbicide mesotrione.